The Difference of Illumination Characteristics of the Sharaf al-Anām in British Library and Leiden University Library - Syamsinar, Anita; Yasmin, Nabila (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2024)
Sḥaraf al-Anām is a prominent mawlīd text traditionally recited during the commemoration of Prophet Muhammad’s birth. This text enjoys widespread composition and utilization across the Muslim world, including Southeast Asia. The manuscript of Sḥaraf al-Anām is typically adorned with decorative ornaments encircling the text. This study investigates the ornamental illumination of two Sḥaraf al-Anām manuscripts housed in the EAP British Library and the Digital Collections of Leiden University Libraries. The former manuscript originates from Sri Lanka, while the provenance of the latter remains unidentified. Both manuscripts present Arabic text with interlinear Malay translations and are aesthetically decorated with diverse styles and patterns. The study analyzed the structural features, ornamental patterns and color designs of the illuminations in these manuscripts. It further explores the potential influences that may have contributed to the presence of such illuminations. This study found notable distinction as observed in the illumination characteristics between the Sḥaraf al-Anām in the EAP British Library collection and that in the Digital Collection of Leiden University Libraries. The comparison suggests that factors such as the provenance of the manuscripts, the artistic quality of the illuminator and the inherent creativity in the work may have contributed to this distinction. This study underscores the importance of these factors in understanding the diversity and richness of manuscript illumination in the Muslim world.